Pengaruh Kepemimpinan Transformasional Disiplin Kerja terhadap Kinerja Karyawan (Management Analysis Journal, 2014)
The research is to analyze the influence of leadership transformational, motivation and discipline on the employees work performance. Sample in this research totaled 54 employees. Sampling techniques using nonprobability sampling and the sampling technique is saturated so the entire population used samples. Variable this research consisting of leadership transformational, motivation, discipline and performance. Data collection methods used were questionnaires. Analysis of the data used is descriptive analysis of the percentage, multiple linear regression analysis and the coefficient of determination with SPSS 21. The results showed transformational leadership, motivation and discipline work simultaneously affect the performance of the employee. This research is expected to enter for the KSU Prima Mandiri Pati to improve the performance of employees by means of a leaders capable of being wise in any decision making so that more employees are disinclined toward its leader. Besides leader is considered necessary to pay close attention to more of its empolyees by conducting communication to an employee on the outside working hours. Supervision against the employee at the time of the working hours in progress can be minimize errors an employee in worked so as the quality of work that is produced is getting better.